Assessment of the Effects of Newly Fabricated CaO, CuO, ZnO Nanoparticles on Callus Formation Maintenance of Alfalfa (Medicago sativa L.) Under In Vitro Salt Stress - Mustafa Akçay; Merve Simsek Geyik; Busra Yazicilar; Fatma Boke; Hayrunnisa Nadaroglu; Okkes Atıcı; İsmail Bezirganoğlu (Agronomy)
Nanoparticles play an important role in plant response to abiotic stresses including salt stress. In this study, the physiological and histological responses of CuO, ZnO, and CaO nanoparticle (NP) applications on callus tissues developed from two alfalfa lines (Erzurum and Muş) exposed to salt (NaCl) stress were evaluated. The NPs were synthesized from the extracts obtained from healthy walnut shells using the green synthesis approach and then characterized by Scanning Electron Microscopy (SEM) and X-ray diffraction analysis (XRD). The leaf explants were placed in an MS medium containing 4 mg L−1 2,4-D (2,4-dichlorophenoxyacetic acid), 50 mM NaCl, and 0.8 ppm of NPs for 1 month in the dark. CaO NP is determined to be more effective than CuO and ZnO in callus induction from leaf explants. Malondialdehyde (MDA) content was higher in the callus treated with 0.8 ppm CuO NP + 50 mM NaCl compared to other treatments. The callus induction stage, without salt treatments, showed the best results with 0.8 ppm CaO NPs for both H2O2 levels and peroxidase (POX) activity compared to the other NPs. The highest protein rate was obtained from the callus induction stage and callus formation stage after 50 mM treatment NaCl with 0.8 ppm CuO. The LCSM results displayed, under in vitro conditions, that the treatment of NPs can greatly suppress the negative effects of salt stress on calli samples. SEM analysis supported the results obtained by laser scanning confocal microscopy (LSCM) analysis. Our findings suggest that CuO, CaO, and ZnO NPs can offer a simple and effective method to protect alfalfa callus from NaCl stress severity. Furthermore, these NPs, particularly CaO, hold potential for broader application and should be evaluated under various abiotic conditions beyond salt stress.